2016
DOI: 10.1007/s12603-015-0604-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of Madin-Darby canine kidney (MDCK) cells to epinephrine

Abstract: Catecholamines regulate a variety of cellular functions in the mammalian kidney. The present study was aimed to investigate the differential sensitivity of Madin-Darby Kidney Cells (MDCK cells) to epinephrine in a dose-dependent manner. The loss of adhesion and altered cell shape were observed in MDCK cells. The presence of apoptosis and necrosis were studied by the fluorescence microscope and Confocal Laser Scanning Microscope (CLSM). Scanning Electron Microscope (SEM) analysis showed several surface microvil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In our work, tested catecholamine (1.5 and 3 mg/kg) decreased the PCE/NCE ratio indicating its cytotoxicity in bone marrow. Muthuraman et al [70] showed that adrenaline possessed a cytotoxic effect and affects DNA fragmentation in a dose-dependent manner in MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, tested catecholamine (1.5 and 3 mg/kg) decreased the PCE/NCE ratio indicating its cytotoxicity in bone marrow. Muthuraman et al [70] showed that adrenaline possessed a cytotoxic effect and affects DNA fragmentation in a dose-dependent manner in MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
“…MDCK cells were cultured and grown in 96‐well plates, and allowed to adhere for 24 h at 37°C. Cells were treated with different concentration of aspartame (2, 4, 6, 8, & 10 mM) and omega‐3 fatty acids (250 µM, 500 µM, 750 µM, 1 mM, & 1.25 mM) individual and combined form for 48 h. At the end of treatment, the cell viability was determined .…”
Section: Methodsmentioning
confidence: 99%
“…After 90% cell confluence, the cells were treated with 10 mM of and 1.25 mM of omega‐3 fatty acids. The morphology of MDCK cells was visualized with the Scanning electron microscope (SEM) . Cells were fixed in a fixative containing 2.5% glutaraldehyde/0.1 M PBS for 30 min at 4°C and postfixed with 1% osmium tetroxide for 30 min at room temperature after repeated wash with PBS.…”
Section: Methodsmentioning
confidence: 99%